First Total Synthesis of the Proposed Structure of Pandangolide 1. Issue 25 (3rd July 2018) - Show, Krishanu; Gonnade, Rajesh G.; Kumar, Pradeep
Abstract : The first total synthesis of the proposed structure of pandangolide 1 is reported. The synthesis was carried out using both an organocatalytic approach and a chiral‐pool approach. The required stereochemistry at C‐3 and C‐5 was installed by using an organocatalytic aldol reaction and a stereoselective ketone reduction. The construction of the 12‐membered core was achieved by 2‐methyl‐6‐nitrobenzoic anhydride‐mediated Shiina lactonization. The structure of target molecule was confirmed unambiguously by single‐crystal X‐ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product. Abstract : The first total synthesis of the proposed structure of pandangolide 1 is reported. The structure of the target molecule was confirmed unambiguously by single‐crystal X‐ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product.